Study on mechanical properties of honeycomb pentamode structures fabricated by laser additive manufacturing: Numerical simulation and experimental verification. (15th October 2019) - Zhang, Lei; Song, Bo; Zhao, Aiguo; Liu, Ruijie; Yang, Lei; Shi, Yusheng
Abstract: In this work, the structural design of mimicking the fluids, the morphological characteristics, stress distributions predicted by finite element (FE) method, mechanical properties and deformation mechanisms of pentamode materials (PMs) were systematically investigated. We proposed a two-steps optimization strategy to rationally design PM structures and the dispersion curves confirmed the obtained structural parameters. The designed PM structures made of Ti-6Al-4V powder were fabricated by selective laser melting (SLM). Besides, due to the slight deviations between the SLM-built PM structures and the designed ones, a modified FE model was used to predict the stress distributions and mechanical properties. Furthermore, from quasi-static compression tests, we find that as the strut widths increase, the deformation mechanism of PM structures transfers from plastic to brittle fracture resulting from the size effect, which indicates that PM structures would have a good elastic nature of buckling when the width of struts is small. The critical width of struts of plastic-to-brittle transition was estimated as 0.12 mm. This work would pave the way to structural design and customized mechanical properties of honeycomb pentamode metamaterials.